A Well-Controlled Experimental System to Study Interactions of Cytotoxic T Lymphocytes with Tumor Cells - Neubert, Natalie J.; Soneson, Charlotte; Barras, David; Baumgaertner, Petra; Rimoldi, Donata; Delorenzi, Mauro; Fuertes Marraco, Silvia A.; Speiser, Daniel E. (Frontiers in Immunology, 2016)
While T cell-based immunotherapies are steadily improving, there are still many patients who progress, despite T cell-infiltrated tumors. Emerging evidence suggests that T cells themselves may provoke immune escape of cancer cells. Here we describe a well-controlled co-culture system for studying the dynamic T cell - cancer cell interplay, using human melanoma as a model. We explain starting material, controls and culture parameters to establish reproducible and comparable cultures with highly heterogeneous tumor cells. Low passage melanoma cell lines and melanoma-specific CD8+ T cell clones generated from patient blood were cultured together for up to three days. Living melanoma cells were isolated from the co-culture system by fluorescence-activated cell sorting. We demonstrate that the characterization of isolated melanoma cells is feasible using flow cytometry for protein expression analysis as well as an Agilent whole human genome microarray and the NanoString Technology for differential gene expression analysis. In addition, we identify five genes (ALG12, GUSB, RPLP0, KRBA2 and ADAT2) that are stably expressed in melanoma cells independent of the presence of T cells or the T cell-derived cytokines IFNγ and TNFα. These genes are essential for correct normalization of gene expression data by NanoString. Further to the characterization of melanoma cells after exposure to CTLs, this experimental system might be suitable to answer a series of questions including how the affinity of CTLs for their target antigen influences the melanoma cell response and whether CTL-induced gene expression changes in melanoma cells are reversible. Taken together, our human T cell - melanoma cell culture system is well suited to characterize immune-related mechanisms in cancer cells.